Surrogacy and the Necessity for its Application in Infertility Treatment - MM Akhondi; Z Behjati Ardakani (JRI, 2008)
Introduction: Upon birth of the first IVF baby, the possibility of having a baby by couples who were infertile due to major problems in the reproductive system was materialized. Development of IVF tech-niques has yielded the opportunity to apply surrogacy and gamete or embryo donation procedures in the form of third party reproduction for couples suffering from the lack a major reproductive element. Surro-gacy seems indispensable for the couples who possess all the factors involved in pregnancy but due to lack of functional uterus, they are deprived from having a child. IVF/ICSI has provided the opportunity for such couples to form healthy embryos in laboratories and transfer it to the third party uterus in due time. Surrogacy agreement will be settled whenever a woman announces her readiness for bearing the couple's embryo and undertakes to relinquish the baby to the embryo owners upon delivery. Materials & Methods: Based on the source of ovum in embryo formation, surrogacy will fall into two principal groups, including gestational and conventional surrogacies. However, surrogacy is also classified into various types in terms of third party’s semen or ovum application. The use of these methods with third party interference in the formation and birth of the baby requires significant juridical, legal, ethical and cultural (and even sociological and psychological) considerations. In response to Avicenna Research Institute’s inquires from religious authorities, there is currently a broad consensus among religious scho-lars on authorization of surrogacy in Iran and they reject the right of surrogate mothers to refuse returning the newborn. Unfortunately, due to lack of codified laws, couples inclined to benefits of surrogacy, either withdraw or resort to illegal conducts. For example, according to the current law, the birth certificate will be issued solely under the name of the woman who gives birth to the newborn and with respect to the facts stated, physicians have to violate the law and issue the birth certificate under the name of gamete owners or uterus owners have to be hospitalized under the name of women seeking surrogacy treatment. Conclusion: The settlement of an agreement between couples applying for surrogacy and the uterus owner may raise various legal, cultural or medical issues. Infertility clinics play a key role in supporting health, providing necessary consultations and supervision following the aforementioned mutual agreements. Silence of law and emergence of any disagreement in the treatment procedure may contribute to unresolv-able problems between the two parties. Nowadays, the possibility of using surrogacy treatment across the country on one hand and the grave need of infertile couples to benefit from this technique on the other hand, emphasize the necessity for improvising well-addressed laws and providing the opportunity to resolve the relevant problems in a move to strengthen family foundations. Enhancing public information on ART and developing and providing infertile couples with the possibility to experience parenthood, will contribute to invoke sympathy and generosity among women to participate in an altruistic sacrifice: surrogacy.
Keywords: Surrogacy, In Vitro fertilization, Gestational surrogacy, Conventional surrogacy, Infertile couples